Exploring the dynamics of microalgal diversity in high-rate algal ponds - Nageshwarihy, Krishnamoort; Dey, Baishali; Unpaprom, Yuwalee; Ramaraj, Rameshprabu; Maniam, Gaanty Pragas; Govindan, Natanamurugaraj; Thirugnanam, Arunachalam; Balasubramanian, Paramasivan
Being primary producers, microalgae play an indispensable role in the interactions of biotic and abiotic communities in any aquatic ecosystem and withhold the ability to survive in oligotrophic to eutrophic environments. The changes that occur in the water quality due to municipal, industrial, pharmaceutical, agricultural, and biological wastes lead to variation in the genotype and positive selection of microalgal communities in high-rate algal ponds (HRAPs). This causes the microalgal strains to become resistant to pollutants such as heavy metals, high ion concentrations, and other extremophilic conditions and makes them utilize the pollutants as nutrients for their growth. A comprehensive change in algal communities could be seen with the change in environmental conditions of open ponds. Conversely, microalgal biomass has numerous applications such as biofertilizer, production of biodiesel, and metabolites. Therefore, it is essential to study the dynamics of microalgae pertaining to fluctuation in the nutrient composition and environmental conditions. The present review focuses on the algal ecology, community variation, and its interaction with bacterial consortia in relation to the wastewater composition. Performance of dominant algal species during the nutrient recovery from wastewaters has been elucidated. Environmental and operational parameters that act as the major drivers in community change have also been detailed. Impact of the mutualistic interaction between the algal and bacterial community have a direct impact over the waste remediation and bioenergy production process. Understanding the feasibility of maintaining the desired algal species would improve the overall performance of the open ponds making algal technology a commercial reality.